ANALISIS KETERSEDIAAN DAN KEBUTUHAN RUANG TERBUKA HIJAU PUBLIK DI KOTA MANADO (Analysis the Availability and Needs of Public Green Open Space of Manado City) - Grace A. Kairupan; Tommy F. Lolowang; Sherly Jocom (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
Manado with the activities of infrastructure development and the approximate increase in the area of settlements increasingly faster due to the rate of population growth, while the limited area of the city requires environmental balancing existence such as the provision of public green open space to create a sustainable city. The purpose of this study is to analyze the availability of public green open space, analyzing the needs of public green open spaces and the adequacy of public green open spacesin Manado city.The data in this research consisting of primary and secondary.Primary data is derived from field observations and secondary data is derived from related institute.Data were analyzed by using Geographic information system (GIS) refers to regional spatial plan of Manado city year 2014-2034 and based on the total of population that refers to regulation of Minister of Public Works No. 05/PRT/M/2008.The result of this research indicates that from the total area of 15726.03 hectares, Manado city has the availability of green open space of 1537.02 hectares while, the needs on regional spatial plan of Manado city stated for 3848.16 hectares. Manado city would still require additional expansion area of green open space of 2311,14 hectares.Based on total of population, sub-districts that has been provided for the provisions of public regional spatial plan only Bunaken, Malalayang and Mapanget..Keywords: Availability, Needs, Public Green Open Space